Production of lotion using neem (Azadirachta Indica A. Juss) extract - Ghazali, Norliza; Jaafar, Aina Syazwana; Mohd Fauzi, Farah Raihana; Mohd Fauzee, Nurfazlina Farisah (Penerbit UTHM, 2020)
Nowadays, the most emerging disease which is arthropod borne disease cannot be prevented from vaccines and become a potential threat especially in tropical world such as America, Africa and Asia and has become a trend (Al-Hashemi et al., 2016; Biswas et al., 2002; Brian et al., 2011). One of the preventive measures is by using extracted neem oil blended into lotions for daily usage. According to Ayurveda medicine, neem (AzadirachtinIndica A. Juss) oil is widely used as a pesticide agent in India which reduce insect feeding and acts a repellent (Costa et al., 2017; Dubey et al., 2014). World Health Organization (WHO) and United Nation Environment Programme (UNEP) 1989 identified neem as an environmentally powerful natural pesticide, considered to be one of the most promising tress of the 21st Century for its great potential in pest management, environment protection and medicine (Costa et al., 2017).